Development of corporate social responsibility as a way to combat raiding - Loktionova, Ya.; Gorbenko, S. (Ways to Improve Construction Efficiency, 2023)
The construction industry in Ukraine plays an important role in stimulating economic growth, urban development and job creation. However, it also faces significant challenges that undermine its potential, including legal instability, weak institutional frameworks and the increased threat of raider takeovers. The article presents a comprehensive analysis of the construction market in Ukraine with a focus on the impact of raider activity on economic security and social responsibility.The study begins with an overview of the Ukrainian construction market, analyzing its key characteristics, growth drivers and challenges. The importance of the sector for the Ukrainian economy is emphasized, attention is paid to its external development in GDP, employment and urbanization. available its potential, the market requires war, systemic vulnerabilities, including corruption, regulatory gaps and the lack of enforcement of property rights.The phenomenon of raider takeovers, which involve the illegal seizure of construction sites, real estate or companies using fraudulent methods or using loopholes in the legislation, is investigated. In recent years, this activity has intensified, undermining the construction sector and posing threats to economic security, investor confidence and social stability. The study classifies raider attacks into different types, such as fraudulent court decisions, corporate raiding and abuse of administrative powers, and examines their root causes.The study examines the study of raider attacks on economic activity, focusing on such parameters as security market instability, loss of investor confidence and capital flight due to obvious risks in the construction sector, project failures, delays, overspending and cancellation of infrastructure and housing projects, institutional weaknesses, and the erosion of trust in legal and regulatory systems, which increases systemic vulnerability.To address these challenges, the article proposes a multifaceted approach aimed at strengthening economic security and ensuring social responsibility in the Ukrainian construction market. Key recommendations include improving legislation to protect property rights, simplifying the procedure for obtaining construction permits and eliminating legal loopholes used by raiders, building support for law enforcement, judicial and regulatory bodies to prevent and effectively regulate raider activities, facilitating the implementation of digital tools and a platform to increase transparency in property transactions, project management and stakeholder communication, and encouraging construction companies to implement CSR practices that provide an advantage in ethical business conduct, community engagement and environmental sustainability.This study aims to improve the understanding of the interplay between economic security, social responsibility and systemic risks in the Ukrainian construction industry. It provides a roadmap for interested parties that want to mitigate the consequences of raider attacks and create a safer and more equitable environment for development.